Effects of exercise and manual therapy on pain associated with hip osteoarthritis: a systematic review and meta-analysis. Issue 8 (26th November 2015) - Beumer, Lucy; Wong, Jennie; Warden, Stuart J; Kemp, Joanne L; Foster, Paul; Crossley, Kay M
Abstract : Aim: To explore the effects of exercise (water-based or land-based) and/or manual therapies on pain in adults with clinically and/or radiographically diagnosed hip osteoarthritis (OA). Methods: A systematic review and meta-analysis was performed, with patient reported pain assessed using a visual analogue scale (VAS) or the Western Ontario and McMaster Universities Arthritis Index (WOMAC) pain subscale. Data were grouped by follow-up time (0–3 months=short term; 4–12 months=medium term and; >12 months=long term), and standardised mean differences (SMD) with 95% CIs were used to establish intervention effect sizes. Study quality was assessed using modified PEDro scores. Results: 19 trials were included. Four studies showed short-term benefits favouring water-based exercise over minimal control using the WOMAC pain subscale (SMD −0.53, 95% CI −0.96 to −0.10). Six studies supported a short-term benefit of land-based exercise compared to minimal control on VAS assessed pain (SMD −0.49, 95% CI −0.70 to −0.29). There were no medium (SMD −0.23, 95% CI −0.48 to 0.03) or long (SMD −0.22, 95% CI −0.51 to 0.06) term benefits of exercise therapy, or benefit of combining exercise therapy with manual therapy (SMD −0.38, 95% CI −0.88 to 0.13) when compared to minimal control. Conclusions: Best available evidence indicates that exercise therapy (whether land-based or water-based) is more effective than minimal control in managing pain associated with hip OA in the short term. Larger high-quality RCTs are needed to establish the effectiveness of exercise and manual therapies in the medium and long term.